0383 Use of an O*NET based job exposure matrix to predict prevalence of Carpal Tunnel Syndrome in a large pooled cohort. (23rd June 2014) - Marie Dale, Ann; Zeringue, Angelique; Harris-Adamson, Carisa; Thiese, Matt; Bao, Stephen; Burt, Sue; Merlino, Linda; Garg, Arun; Eisen, Ellen; Gerr, Fred; Hegmann, Kurt; Kapellusch, Jay; et al.
Abstract : Objectives: To determine if job title based physical exposure measures predicted prevalent carpal tunnel syndrome (CTS) in a large pooled cohort of workers. Method: We pooled baseline examination data from six prospective cohort studies, restricting analyses to those employed at least 1 year. CTS was defined as median neuropathy plus typical symptoms. Physical exposure estimates for static strength, dynamic strength, time spent making repetitive motions, and time handling objects were extracted from the Occupational Network (O*NET) database using Standard Occupational Classification codes based on reported job title. Three exposure categories of high force/ high repetition, low force/ low repetition, and mixed high and low exposures were entered into logistic regression models adjusting for age, gender, body mass index (BMI), diabetes, rheumatoid arthritis, employed time and study site. Results: Of 3562 in the pooled cohort, 7.6% met a prevalent CTS definition with mean employed time of 7.9 years (SD 8.2). Compared to subjects with low job requirements for dynamic strength and repetitive motion, those with mixed exposures or high exposures showed increased prevalence of CTS (OR 1.46; 95% CI: 1.01–2.11 and OR 2.32; 95% CI: 1.15–4.67, respectively). Similar dose dependent associations of combined exposures were shown for all exposure combinations tested, with high/high combinations having the largest effect sizes (OR range 2.32–3.17) relative to the low force/low repetition exposure combinations. Conclusions: Use of job-title based exposures was useful for demonstrating associations with prevalent CTS. Jobs with combined high exposures of force and repetition showed consistently greater risk of CTS compared to jobs with lower exposure levels.